Pesantren: Dinamika dan Perkembangan - Dalimunthe, Rasyid Anwar (Al-Fikru: Jurnal Ilmiah, 2019)
The establishment of the Islamic Boarding School was also initially initiated by Wali Songo, initiated by Sheikh Maulana Malik Ibrahim who is from Gujarat India. During the Dutch colonial era, in various ways the colonialists tried to discredit Islamic education managed by natives, including pesantren. Ki Hajar Dewantara alone as the National Education figure and the first Minister of Indonesian Teaching Education stated that Islamic boarding schools are the basis of national education, because they are in accordance with the spirit and personality of the Indonesian people. pesantren education today has received the same attention from the government, especially the Ministry of Religion. At present it has become a separate directorate, namely the directorate of religious education and Islamic boarding school which aims to optimally improve the services of Islamic boarding schools to the community.